2001
DOI: 10.1063/1.1337802
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical description of quantum coherence effects and their quenching: A forward–backward initial value representation study

Abstract: The forward-backward ͑FB͒ version of the semiclassical ͑SC͒ initial value representation ͑IVR͒ is used to study quantum coherence effects in the time-dependent probability distribution of an anharmonic vibrational coordinate and its quenching when coupled to a thermal bath. It is shown that the FB-IVR accurately reproduces the detailed quantum coherent structure in the weak coupling regime, and also describes how this coherence is quenched with an increase of the system-bath coupling and/or the bath temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 72 publications
5
89
0
Order By: Relevance
“…As a final note, in this subsection we have confirmed that for nuclear DOF, the distribution of coordinates 45 or momenta 10 produced by methods that employ mean-field Ehrenfest-like forces such as LSC-IVR can be qualitatively in error. As we will demonstrate in Subsection III B this can have profound problems for predicting electronic state relaxation dynamics with such approaches, though these problems are mitigated to a significant extend for some mean-field like methods such as the PLDM propagation approach.…”
Section: A Nuclear Phase Space Distributions From Linearized and Itmentioning
confidence: 53%
See 1 more Smart Citation
“…As a final note, in this subsection we have confirmed that for nuclear DOF, the distribution of coordinates 45 or momenta 10 produced by methods that employ mean-field Ehrenfest-like forces such as LSC-IVR can be qualitatively in error. As we will demonstrate in Subsection III B this can have profound problems for predicting electronic state relaxation dynamics with such approaches, though these problems are mitigated to a significant extend for some mean-field like methods such as the PLDM propagation approach.…”
Section: A Nuclear Phase Space Distributions From Linearized and Itmentioning
confidence: 53%
“…These well-known disadvantages of mean-field like methods can be addressed by surface hopping schemes 1, 46 but many such approaches involve ad hoc steps in their implementation. The forward-backward IVR (FB-IVR) approach 10,45,47 provides a relatively inexpensive alternative that is derivable from first principles and can solve these problems in many situations. The iterative linearized short time approximate propagation methods outlined here are also based on well-defined approximations and overcome the problems associated with meanfield propagation and can be made very competitive in computational cost.…”
Section: A Nuclear Phase Space Distributions From Linearized and Itmentioning
confidence: 99%
“…The analytic and computational results shed new light on decoherence, dynamics of quantum entanglement, and quantum chaos. This study is also of interest to semiclassical decoherence studies [9], e.g., semiclassical descriptions of intrinsic decoherence dynamics in large molecular systems [2]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Although the above "time-dependent" approach has been widely used for the explicit computation of thermal rate constants [40][41][42], it presents many numerical problems. In particular,…”
Section: The Time-dependent Approachmentioning
confidence: 99%